Peningkatan Kesadaran Mahasiswi Akan Sampah Gelas Minuman Plastik Di Universitas Pelita Harapan Dengan Pendekatan Desain Produk - Devanny Gumulya; Irvin Aditya Parapak; Luther Tjunawan; Nabila Andini Nareswari; Indarto Indarto; Yosefin Suhanto (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
We currently live in the constantly changing urban life that has created unsurmountable waste, as we used to buy, use, and throw when it reaches its end of life. With this habit, Indonesia has become the second largest plastic waste contributor in the world. The product design students who are millennials generation must be aware of this issue, as they are the future of our nation. With the product design approach, the students are asked to recycle the plastic waste that is polluting UPH’s environment. From the interview and observation, founded that there is 6.000 plastic cup used monthly. The plastic cup is categorized under polypropylene and polyethylene plastic in which both are thermoplastic, a kind of plastic that is pliable when given certain heat. The process starts with collecting, sorting, cleaning; then the waste is ready to be recycled with many exploration techniques with non-heated or heat process using a hot press machine on 1200C - 1600C to get new material that has good aesthetic and structure quality. After the waste is successfully made into functional products, the results are socialized to students from other disciplines through a workshop in which to participate he or she must bring their own plastic waste. This community service has reduced plastic cup waste in UPH by 1% and raising millennials' awareness about plastic waste. Hopefully, the process and the workshop program can change their perception that plastic cups are not waste but as a material that ready to be used again and can be made into functional products.